HUKUM ISLAM DAN PROBLEMATIKA SOSIAL; TELAAH TERHADAP BEBERAPA HUKUM PERDATA ISLAM DALAM KOMPILASI HUKUM ISLAM DI INDONESIA - Aris; Muhammad Sabir (DIKTUM: Jurnal Syariah dan Hukum, 2020)
Islamic law cannot be separated from the context of the social life of Muslims in Indonesia. This paper discusses the material analysis of the Compilation of Islamic Law which consists of Marriage, Inheritance and Waqf associated with the social problems of Muslims in Indonesia. The compilation of Islamic Laws received juridical justification with Presidential Instruction No. 1 of 1991, is a form of political Islamic law in Indonesia that is less than perfect because it does not go through the legislation of the legislative body and is a shortcut in establishing and positivating Islamic law. The material of KHI, especially marriage and inheritance, is considered inadequate to accommodate the social problems of Indonesian Muslims.